PENGEMBANGAN BUKU PANDUAN ALAT MUSIK PIANIKA PADA PEMBELAJARAN SBdP UNTUK SISWA SEKOLAH DASAR NEGERI 1 DADAPAN - Mara, Istiana; Gutama, Andika; Rahayunita, Cicilia Ika (Sindoro: Cendikia Pendidikan, 2024)
In the learning of Cultural Arts and Skills (SBdP) focusing on understanding tempo markings and pitch, particularly in the musical art of playing the melodica, students find it difficult to grasp the material being taught, and there is a lack of proper time management. Additionally, not all teachers have qualifications in musical arts. This type of research is qualitative, conducted through interviews, observations, and validation questionnaires from experts in content, media, and language. From the study on the Development of a Melodica Instruction Guide for SBdP Learning in Elementary Schools, through the validation testing process, the following results were obtained: media experts rated it with an average feasibility percentage of 90%, content experts 89%, and language experts 93%, all categorized as "very feasible." For the practicality test, teachers’ responses averaged 96%, and students' responses averaged 93%, both deemed "practical without revision" for use. Thus, it can be concluded that the development of the melodica instruction guide, after going through the product creation stages and passing feasibility and practicality tests through expert validation and feedback from teachers and students, is declared feasible and practical for use. Pada pembelajaran SBdP materi memahami tanda tempo dan tinggi rendah nada khususnya seni musik pianika, siswa sulit memahami materi yang diajarkan dan kurangnya manajemen waktu yang tepat. Serta tidak semua guru memiliki kualifikasi dalam seni musik. penelitian kualitatif yang dilakukan melalui wawancara, observasi, dan angket validasi dari para ahli materi, media, dan bahasa adalah jenis penelitian ini. Dari penelitian Pengembangan Buku Panduan Alat Musik Pianika Pada Pembelajaran SBdP Untuk Sekolah Dasar, melalui proses uji validasi di antaranya: ahli media memiliki rata-rata persentase tingkat kelayakan 90% ahli materi 89% ahli bahasa 93% dinyatakan “sangat layak”. Adapun uji kepraktisan: respons guru memperoleh rata-rata persentase 96% dan respons siswa 93% dinyatakan “praktis tanpa revisi” untuk digunakan. Berdasarkan paparan di atas, dapat nyatakan bahwa pengembangan buku panduan alat musik pianika setelah melalui tahapan pembuatan produk dan melewati pengujian kelayakan, kepraktisan melalui proses uji validasi ahli, respons guru dan siswa menyatakan layak dan praktis untuk dipakai.